Visual Semiotic Analysis in Farm Animal Vocabulary Educational Videos for Early Childhood - Pertiwi, Annisa Bela; Budiman, Budiman (Mimbar Ilmu, 2025)
In the digital era, animated educational media has become an increasingly effective tool in early childhood learning. Nevertheless, research on how visual signs in educational videos can support the learning process remains very limited. This study analyzes the use of visual signs in the Belajar Kosakata video. A descriptive qualitative method was employed, using visual observation and documentation techniques. The research instrument consisted of a visual sign analysis grid developed to categorize the use of icons, indexes, and symbols in educational videos based on Peirce’s semiotic theory. The analysis was conducted on 21 image clips, consisting of 7 icons, 12 indexes, and 5 symbols, selected based on their relevance in delivering educational content. The findings reveal that indexes are the most dominant sign in the analyzed samples, appearing 12 times (57.14%), in the form of sounds and visual effects that link video elements to the concepts being taught. Icons appear 7 times (33.33%) as visual representations of animals resembling their real forms, while symbols are used 5 times (23.81%) in texts or graphic elements that introduce vocabulary. The total percentage exceeds 100% because some images contain more than one type of sign simultaneously. These findings indicate that a semiotic approach in educational videos helps enhance children’s understanding through the combination of visual and auditory signs.